Composite positive plate as well as preparation method and application thereof

By spraying a polymer coating with gradient lithium borate on the positive electrode sheet of an all-solid-state lithium-ion battery, a three-dimensional porous structure is constructed using 3D printing technology, which solves the problems of small contact area and large interface impedance between the solid electrolyte and the electrode, and significantly improves the ion transmission rate and electrochemical performance of the battery.

CN119695157APending Publication Date: 2025-03-25深圳毅华新能源有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411890534.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Due to the all-solid-solid point contact between the solid electrolyte and the electrode, all-solid-state lithium-ion batteries have small contact areas, poor interface contact, obstructed ion transmission, and large interface impedance, which affects the internal resistance, cycling performance and rate performance of the battery.

Method used

A polymer coating with gradient lithium borate is sprayed on the surface of the positive electrode sheet away from the current collector. A coating with a three-dimensional porous structure is constructed through 3D printing technology to reduce interface impedance and improve interface stability.

Benefits of technology

Effectively reduce the impedance of the positive electrode/electrolyte interface, improve the interface stability on the positive electrode side, improve the ion transmission rate and electrochemical performance of the battery, and achieve stable circulation of 900 cycles at room temperature 2C, with a capacity retention rate of >80%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005200545450000091
    Figure BDA0005200545450000091
  • Figure HDA0005200545460000011
    Figure HDA0005200545460000011
  • Figure HDA0005200545460000012
    Figure HDA0005200545460000012
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a composite positive plate as well as a preparation method and application thereof. The composite positive plate comprises a positive plate and a coating located on the surface of the side, away from a current collector, of the positive plate, the coating comprises 2-5 polymer layers, each polymer layer comprises lithium borate, the concentration of the lithium borate in the polymer layers is in a gradient reduction trend, and the concentration of the lithium borate in the polymer layer closest to the positive plate is the highest. The prepared lithium solid-state battery is low in interface impedance, high in ion migration rate and small in charge and discharge process polarization, can stably circulate for 900 circles at the room temperature 2C rate, and has the capacity retention rate gt; and the lithium ion battery can be stably circulated for 200 circles at a high-load positive electrode of 10mg cm <-2 >. 82% of the initial capacity of the positive electrode assembled bag type battery with the area capacity of 3.5 mAh cm <-2 > can be kept after 100 times of circulation, the coulombic efficiency is improved to 99.8 + / -0.1%, and the positive electrode assembled bag type battery has great industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a composite positive electrode sheet and a preparation method and application thereof. Background Art

[0002] All-solid-state batteries based on solid electrolytes can effectively prevent lithium dendrites from penetrating the diaphragm and causing a short circuit in the battery, and are one of the excellent alternatives to electrolytes. Polymer solid electrolytes (SPEs) have good flexibility, can achieve sufficient interface contact with electrode materials, have low interface resistance, are easy to process and prepare, and are compatible with existing liquid battery assembly equipment. They are considered to be the most promising electrolytes for solid-state batteries. However, at present, the solid electrolyte and the electrode are all solid-solid point contacts, resulting in a small contact area between the two, poor interface contact, obstructed ion transmission, and large interface impedance, which seriously affects the transmission of ions, causing a sharp increase in the internal resistance of all-solid-state lithium-ion batteries, and deterioration in battery cycle performance and rate performance. In addition, solid electrolytes also have the problem of poor compatibility with the positive electrode interface. Due to the lack of electrolyte infiltration inside the positive electrode, the ion transmission performance is also poor. During the charge and discharge process, the volume of each material expands and contracts, which causes the interface to separate easily.

[0003] Prior art CN 111952597 A discloses a composite positive electrode sheet and its preparation method, and a solid-state battery, wherein a polymer and a lithium salt are dissolved in a solvent to form a mixed slurry; and then the mixed slurry is scraped and coated on the surface of the positive electrode sheet away from the current collector, and dried to form a protective layer to avoid direct contact between the positive electrode material and the solid electrolyte and reduce the interface impedance. However, the solid electrolyte prepared by this prior art is difficult to accurately control the thickness, and the polymer and the electrode interface cannot achieve large-area effective contact, and it is difficult to achieve a complex three-dimensional structure.

[0004] Prior art CN 118867413 A discloses a solid-state battery and a preparation method thereof, which uses 3D printing to print the entire solid-state battery cell in an integrated manner to obtain a solid-state battery cell, which can achieve batch production. However, the electrochemical performance of the solid-state battery using integrated printing is poor and stable long-cycle performance cannot be achieved. Summary of the invention

[0005] The object of the present invention is to provide a composite positive electrode sheet and a preparation method and application thereof, so as to effectively reduce the impedance of the positive electrode / electrolyte interface and improve the interface stability of the positive electrode side.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A composite positive electrode sheet comprises a positive electrode sheet and a coating located on the surface of the positive electrode sheet away from a current collector, wherein the coating comprises 2-5 polymer layers, each polymer layer comprises lithium borate, and the concentration of lithium borate in the polymer layers decreases in a gradient, and the concentration of lithium borate in the polymer layer closest to the positive electrode sheet is the highest.

[0008] The present invention found that the positive electrode side of the battery requires higher electrochemical stability and the ability to inhibit lithium dendrites. Therefore, a high concentration of lithium salt is used in the coating close to the positive electrode side, which helps to improve the electrochemical window and mechanical strength of the electrolyte and provide better dendrite inhibition ability and high voltage resistance.

[0009] In a preferred embodiment, the polymer layer is formed by 3D printing of polymer coating.

[0010] In a preferred embodiment, the polymer coating comprises a polymer matrix solution and lithium borate; the polymer matrix solution comprises a polymer matrix and a phosphate ester solvent.

[0011] In a preferred embodiment, the polymer matrix is ​​selected from any one or two of polyvinylidene fluoride (PVDF-based) and poly(vinylidene fluoride-hexafluoropropylene) copolymer.

[0012] Compared with other polymers, PVDF has a wider electrochemical stability window, excellent chemical stability, good mechanical strength and piezoelectricity. It can maintain stable mechanical properties under high pressure and has the advantages of low density, low impedance and high dielectric constant.

[0013] In a preferred embodiment, the molecular weight of the poly(vinylidene fluoride-hexafluoropropylene) copolymer is 300,000-500,000.

[0014] In a preferred embodiment, the molecular weight of polyvinylidene fluoride is 700,000-1,000,000.

[0015] In a preferred embodiment, the lithium borate is selected from any one or both of lithium bis(oxalatoborate) (LiBOB) and lithium difluorooxalatoborate (LiDFOB).

[0016] LiBOB and LiDFOB have good thermal stability, and their decomposition temperature is higher than that of lithium hexafluorophosphate (LiPF6), which is above 240°C. They do not contain fluorine and have high solubility in organic solvents, which reduces pollution to the environment.

[0017] LiBOB and LiDFOB have a high electrochemical window and can form a dense boron-containing polymer as a solid electrolyte interlayer, which helps to improve the voltage platform.

[0018] In a preferred embodiment, the phosphate ester solvent is selected from any one or both of trimethyl phosphate (TMP) and triethyl phosphate (TEP).

[0019] TMP and TEP are flame retardant, high temperature resistant, non-volatile, chemically stable and biodegradable, and are environmentally friendly.

[0020] In a preferred embodiment, the polymer coating comprises 5-15 parts of a polymer matrix solution and 80-95 parts of a phosphate ester solvent.

[0021] In one preferred embodiment, the weight proportion of lithium borate in the polymer coating for preparing the polymer layer closest to the positive electrode is 7-9 parts.

[0022] In a preferred embodiment, the thickness of the polymer layer closest to the positive electrode sheet is 2-10 μm.

[0023] The polymer layer closest to the positive electrode plays a role in constructing an ion transmission channel and decomposing into a film. If the lithium salt concentration of the coating is too high or the thickness is too large, the mechanical strength will be significantly weakened and the growth of lithium dendrites cannot be effectively inhibited. If the lithium salt concentration is too low or the thickness is too small, the ion transmission is insufficient and it is not enough to decompose on the positive electrode side to form a stable and dense interface layer.

[0024] In one preferred embodiment, the weight proportion of lithium borate in the polymer coating used to prepare the polymer layer farthest from the positive electrode is 1-3 parts.

[0025] In one preferred embodiment, the thickness of the polymer layer farthest from the positive electrode sheet is 2-10 μm.

[0026] The polymer layer farthest from the positive electrode sheet contacts the solid electrolyte, provides a relatively smooth lithium salt concentration transition zone, and maintains the uniformity of electrochemical performance. If the lithium salt concentration of the coating is too high or the thickness is too large, the viscosity of the coating will increase and ion transmission will be blocked. If the lithium salt concentration is too low or the thickness is too small, there will be too many pores in the polymer structure, resulting in uneven ion distribution.

[0027] In a preferred embodiment, the coating comprises three polymer layers.

[0028] In a preferred embodiment, the mass proportion of lithium borate in the polymer coating for preparing the intermediate layer is 4-6%.

[0029] In a preferred embodiment, the thickness of the intermediate layer is 4-5 μm.

[0030] The middle layer plays a role of medium gradient and is designed to balance the lithium salt concentration. If the lithium salt concentration of the coating is too low or the thickness is too small, it will not be able to build enough ion channels for transmission, affecting the impedance of the battery. If the lithium salt concentration of the coating is too high or the thickness is too large, the viscosity is too high, which will also affect the transmission of ions.

[0031] In a preferred embodiment, the coating comprises four polymer layers.

[0032] In one preferred embodiment, the weight proportion of lithium borate in the polymer coating used to prepare the polymer layer second closest to the positive electrode is 5.5-6.5 parts.

[0033] In a preferred embodiment, the thickness of the polymer layer that is second closest to the positive electrode sheet is 2-2.5 μm.

[0034] In one preferred embodiment, the weight proportion of lithium borate in the polymer coating used to prepare the third polymer layer closest to the positive electrode is 3.5-5 parts.

[0035] In a preferred embodiment, the thickness of the polymer layer closest to the positive electrode sheet is 2-2.5 μm.

[0036] Based on the same inventive concept, the present invention also claims protection for a method for preparing the composite positive electrode sheet, comprising the following steps: polymer coatings containing different concentrations of lithium borates are sequentially fixed on the surface of the positive electrode away from the current collector through 3D printing gradients, and the polymer coating with the highest lithium borate concentration is printed on the inner side close to the positive electrode to form a gradient structured coating.

[0037] In one preferred embodiment, when 3D printing the coating, each 3D printing nozzle corresponds to a polymer solution with a lithium borate concentration, and the gradient is printed in sequence.

[0038] In a preferred embodiment, the total thickness of the printed coating is 10-25 μm.

[0039] Based on the same inventive concept, the present invention also claims protection for the use of the composite positive electrode sheet in the preparation of solid-state batteries.

[0040] Based on the same inventive concept, the present invention also claims protection for a solid-state battery, including the composite positive electrode sheet.

[0041] In a preferred embodiment, the solid-state battery is a lithium polymer-based solid-state battery.

[0042] In a preferred embodiment, the solid-state battery includes the composite positive electrode sheet, polymer-based solid electrolyte and negative electrode assembled in sequence.

[0043] In a preferred embodiment, the material of the positive electrode sheet is a nickel-cobalt-manganese ternary positive electrode material.

[0044] Compared with the prior art, the beneficial technical effects of the present invention are:

[0045] 1. The present invention adopts a method for modifying the interface coating. A phosphate polymer coating of gradient lithium borate is sprayed on the positive electrode side to improve the positive electrode interface. The present invention adopts a method for modifying the interface coating. A polymer coating of gradient lithium borate is sprayed on the positive electrode side to improve the positive electrode interface. Lithium borate generally has a wide electrochemical window, and a dense boron-containing polymer intermediate layer can be formed during the first discharge process to achieve compatibility with the high-voltage positive electrode. Phosphate esters are used as solvents to dissolve lithium salts and polymer matrices. Compared with traditional electrolyte solvents, they have a higher highest occupied molecular orbital (HOMO) energy level, and can preferentially undergo electrochemical oxidation on the positive electrode surface, thereby forming a protective film on the positive electrode surface. The polymer coating liquid is sprayed on the positive electrode plate by 3D printing, and the prepared polymer coating has a controllable thickness, a stable structure, and a three-dimensional porous structure with a large surface area. The polymer coating is in closer contact with the positive electrode material, which reduces polarization and interface impedance, is conducive to the construction of an ion transport network, and accelerates the number of ion migration. At the same time, through the lithium borate concentration gradient design, the strain of the active material structure can be effectively reduced, the ion transmission path can be optimized, the emergence of ion concentration gradient can be slowed down, and the resistance in the ion transmission process can be reduced, thereby stabilizing the structure of the positive electrode material.

[0046] 2. The preparation method of the present invention is simple, compatible with existing preparation equipment, and easy to mass produce.

[0047] 3. The lithium solid-state battery proposed in the present invention is equipped with a three-dimensional gradient structure polymer coating positive electrode, which has low interface impedance, fast ion migration rate, small polarization during charge and discharge, and can be stably cycled for 900 cycles at 2C rate at room temperature, with a capacity retention rate of >80%, and at a high load positive electrode of 10 mg cm -2 It can stably cycle 200 times, even at an area capacity of 3.5 mAh cm -2 Under the circumstances, the positive electrode assembled pouch-type battery with gradient structure polymer coating can maintain 82% of its initial capacity after 100 cycles, and the Coulomb efficiency is increased to 99.8±0.1%, which is of great industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 A schematic diagram of the structure of a solid-state battery with a gradient concentration of lithium borate prepared in an embodiment of the present invention;

[0049] Figure 2 The room temperature impedance diagram of button cells assembled according to Example 1 of the present invention and Comparative Example 11.

[0050] Figure 3 CV graphs of button cells assembled according to Example 1 and Comparative Example 11 of the present invention.

[0051] Figure 4 The first cycle charge and discharge curves of button batteries assembled in Example 1 and Comparative Example 11 of the present invention are shown.

[0052] Figure 5 The positive electrode in Example 1 of the present invention and Comparative Example 11 is 3.5 mg / cm 2 Room temperature electrochemical performance of assembled coin cells under load.

[0053] Figure 6 The positive electrode in Example 1 of the present invention is 10 mg / cm 2 Room temperature electrochemical performance of assembled coin cells under high load.

[0054] Figure 7 The positive electrode in Example 1 of the present invention is 3.5 mAh / cm 2 Room temperature electrochemical performance of assembled pouch cells at full capacity. DETAILED DESCRIPTION

[0055] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention in various other specific embodiments according to the contents disclosed in the present invention, or any simple changes or modifications made to the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0056] Example 1

[0057] (1) Preparation of polymer coating liquid:

[0058] Gradient 1 solution: 0.25 g poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight average molecular weight of 400,000) and 0.230 g lithium bis(oxalatoborate) LiBOB were dissolved in 2 mL trimethyl phosphate TMP, stirred at 65° C. for 12 h to obtain a polymer coating solution. The mass proportion of LiBOB was 8%.

[0059] Gradient 2 solution: Specifically, 0.25 g poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight average molecular weight of 400,000) and 0.139 g LiBOB were dissolved in 2 mL TMP, stirred at 65° C. for 12 h to obtain a polymer coating solution. The mass proportion of LiBOB was 5%.

[0060] Gradient 3 solution: Specifically, 0.25 g poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight average molecular weight of 400,000) and 0.054 g LiBOB were dissolved in 2.5 mL TMP, stirred at 65° C. for 12 h to obtain a polymer coating solution. The mass proportion of LiBOB was 2%.

[0061] Among them, the phosphate solvent TMP has a higher HOMO energy level than conventional electrolyte solvents, so that electrochemical oxidation can occur preferentially on the positive electrode surface, forming a positive electrode side protective film to stabilize the structure of the positive electrode active material.

[0062] (2) Preparation of positive electrode: Lithium nickel cobalt manganese (LiNi 0.8 Co 0.1 Mn 0.1 O2) was used as the active material, and was evenly mixed with a conductive agent (acetylene black) and a binder [polyvinylidene fluoride (PVDF)] in a mass ratio of 80:10:10, coated on a carbon-coated aluminum foil, and dried in a vacuum drying oven at 80°C for 24 hours to remove the solvent.

[0063] (3) Preparation of polymer coating. The polymer solutions of different gradients are respectively introduced into the liquid nozzles of the corresponding 3D printing equipment, and sprayed on the side of the positive electrode away from the current collector in the order of gradients 1-3. After each concentration gradient of the polymer solution is sprayed, it is dried immediately, and then the next concentration gradient is sprayed, thereby constructing a three-dimensional lithium salt gradient polymer coating. The coating thickness closest to and farthest from the positive electrode is 6μm, the thickness of the middle layer is 3μm, and the total coating thickness is 15μm. The prepared positive electrode sheet with a polymer coating is placed in a dryer between the liquid nozzle and the electrode to remove the solvent, and a modified positive electrode sheet is obtained.

[0064] (4) Preparation of electrolyte: 0.4 g poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight average molecular weight of 400,000) and 0.4 g LiTFSI were dissolved in 4 mL DMF solution and stirred at 50 °C for 8 h until completely dissolved. The obtained solution was uniformly cast into a film and dried in a vacuum drying oven at 60 °C for 24 h to obtain a solid electrolyte.

[0065] (5) Selection of negative electrode: 450 μm lithium metal sheet was used as the negative electrode.

[0066] (6) Assembly of lithium solid-state batteries: Figure 1 As shown in the schematic diagram, the coated positive electrode sheet, the negative electrode sheet, and the solid electrolyte are assembled into a lithium solid-state battery (button battery) for room temperature impedance, CV, and charge and discharge performance tests.

[0067] (7) Assembly of lithium soft-pack batteries: The coated positive electrode sheet was cut into 43×56 mm, the negative electrode sheet was cut into 45×58 mm, and the solid electrolyte was cut into 50×65 mm. The sheets were stacked and sealed in the order of positive electrode, solid electrolyte, and negative electrode under an inert atmosphere and placed in a cabinet for pouch battery cycle performance testing.

[0068] Example 2

[0069] Example 1 was repeated, except that: in step (1), the mass of LiBOB in the gradient 1 solution was changed to 0.199 g. The mass proportion of LiBOB was 7%. The mass of LiBOB in the gradient 2 solution was changed to 0.110 g. The mass proportion of LiBOB was 4%. The mass of LiBOB in the gradient 3 solution was changed to 0.027 g. The mass proportion of LiBOB was 1%.

[0070] Example 3

[0071] Example 1 was repeated, except that: in step (1), the mass of LiBOB in the gradient 1 solution was changed to 0.262 g. The mass proportion of LiBOB was 9%. The mass of LiBOB in the gradient 2 solution was changed to 0.169 g. The mass proportion of LiBOB was 6%. The mass of LiBOB in the gradient 3 solution was changed to 0.082 g. The mass proportion of LiBOB was 3%.

[0072] Example 4

[0073] Example 1 was repeated, with the only difference being that in step (3), the 3D printing device controlled the total thickness of the polymer coating to be 10 μm, and the thickness of each layer was set in the same proportion as in Example 1.

[0074] Example 5

[0075] Example 1 was repeated, with the only difference being that in step (3), the 3D printing device controlled the polymer coating thickness to be 20 μm, and the thickness of each layer was set in the same proportion as in Example 1.

[0076] Example 6

[0077] Example 1 was repeated, except that in step (3), the 3D printing device controlled the polymer coating thickness to be 25 μm, and the thickness of each layer was set in the same proportion as in Example 1.

[0078] Example 7

[0079] Example 1 was repeated, with the only difference being that when designing the gradient solution coating in step (1), the lithium borate was replaced by LiDFOB instead of LiBOB.

[0080] Example 8

[0081] Example 1 was repeated, with the only difference being that in step (1) when designing the gradient solution coating, TEP was used as the solvent instead of TMP.

[0082] Example 9

[0083] Example 1 was repeated, except that: in step (1), when designing the gradient solution coating, LiDFOB was used as the lithium borate instead of LiBOB, and TEP was used as the solvent instead of TMP.

[0084] Comparative Example 1

[0085] Example 1 was repeated, with the only difference being that the same gradient solution was used in the preparation of the positive electrode polymer coating liquid in step (1). Specifically, 0.25 g of poly (vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight-average molecular weight of 400,000) and 0.054 g of LiBOB were dissolved in 2 mL of TMP, stirred at 65°C for 12 h to obtain a polymer coating liquid. The mass proportion of LiBOB was 2%. The obtained polymer solution was passed through the liquid nozzle of the corresponding 3D printing equipment and sprayed on the side of the positive electrode away from the current collector to construct a lithium salt gradient polymer coating. The total coating thickness was 15 μm.

[0086] Comparative Example 2

[0087] Example 1 was repeated, with the only difference being that the same gradient solution was used in the preparation of the positive electrode polymer coating liquid in step (1). Specifically, 0.25 g of poly (vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight-average molecular weight of 400,000) and 0.139 g of LiBOB were dissolved in 2 mL of TMP, stirred at 65°C for 12 h, to obtain a polymer coating liquid. The mass proportion of LiBOB is 5%. The obtained polymer solution was passed through the liquid nozzle of the corresponding 3D printing equipment and sprayed on the side of the positive electrode away from the current collector to construct a three-dimensional lithium salt gradient polymer coating. The total coating thickness is 15 μm.

[0088] Comparative Example 3

[0089] Example 1 was repeated, with the only difference being that the same gradient solution was used in the preparation of the positive electrode polymer coating liquid in step (1). Specifically, 0.25 g of poly (vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight-average molecular weight of 400,000) and 0.230 g of LiBOB were dissolved in 2 mL of TMP, stirred at 65 ° C for 12 h, and a polymer coating liquid was obtained. The mass proportion of LiBOB was 8%. The obtained polymer solution was passed into the liquid nozzle of the corresponding 3D printing equipment, sprayed on the side of the positive electrode away from the current collector, and a three-dimensional lithium salt gradient polymer coating was constructed. The total coating thickness was 15 μm.

[0090] Comparative Example 4

[0091] Example 1 was repeated, except that: in step (1), when designing the gradient solution coating, the solvent used was N-methylpyrrolidone (NMP) instead of TMP. The polymer solutions with different lithium salt gradients were respectively introduced into the liquid nozzles of the corresponding 3D printing equipment to construct a three-dimensional lithium salt gradient polymer coating. The total thickness of the coating was 15 μm.

[0092] Comparative Example 5

[0093] Example 1 was repeated, with the only difference being that in step (3), the 3D printing device controlled the polymer coating thickness to be 5 μm.

[0094] Comparative Example 6

[0095] Example 1 was repeated, with the only difference being that in step (3), the 3D printing device controlled the polymer coating thickness to be 8 μm.

[0096] Comparative Example 7

[0097] Example 1 was repeated, with the only difference being that in step (3), the 3D printing device controlled the polymer coating thickness to be 30 μm.

[0098] Comparative Example 8

[0099] Example 1 was repeated, with the only difference being that in step (3), the 3D printing device controlled the polymer coating thickness to be 40 μm.

[0100] Comparative Example 9

[0101] Example 1 was repeated, except that: in step (1), when designing the gradient solution coating, LiPF6 was used instead of LiBOB as the lithium salt. The polymer solutions with different lithium salt gradients were respectively introduced into the liquid nozzles of the corresponding 3D printing equipment to construct a three-dimensional lithium salt gradient polymer coating. The total coating thickness was 15 μm.

[0102] Comparative Example 10

[0103] Example 1 was repeated, except that: in step (1), when designing the gradient solution coating, LiBF4 was used instead of LiBOB as the lithium salt. The polymer solutions with different lithium salt gradients were respectively introduced into the liquid nozzles of the corresponding 3D printing equipment to construct a three-dimensional lithium salt gradient polymer coating. The total thickness of the coating was 15 μm.

[0104] Comparative Example 11

[0105] Example 1 was repeated, except that: in step (3), when preparing the polymer coating, a solution casting method was used instead of 3D printing spraying technology. The polymer matrix, gradient lithium salt and organic solvent were mixed evenly to obtain slurries with different gradients. The slurries were cast on the positive electrode side in order from high to low concentration, dried, and formed into a film to obtain a modified coated positive electrode. The total thickness of the coating was 15 μm.

[0106] Comparative Example 12

[0107] Example 1 was repeated, with the only difference being that when designing the gradient solution coating in step (1), LiDFOB was used instead of LiBOB as the lithium borate. The same gradient solution was used in the preparation of the positive electrode polymer coating liquid. Specifically, 0.25 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight-average molecular weight of 400,000) and 0.139 g of LiDFOB were dissolved in 2 mL of TMP, stirred at 65°C for 12 h to obtain a polymer coating liquid. The mass proportion of LiDFOB was 5%. The obtained polymer solution was passed into the liquid nozzle of the corresponding 3D printing equipment and sprayed on the side of the positive electrode away from the current collector to construct a three-dimensional lithium salt gradient polymer coating. The coating thickness was 15 μm.

[0108] Comparative Example 13

[0109] Example 1 was repeated, with the only difference being that when designing the gradient solution coating in step (1), TEP was used as the solvent instead of TMP. The same gradient solution was used in the preparation of the positive electrode polymer coating liquid. Specifically, 0.25 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight-average molecular weight of 400,000) and 0.126 g of LiBOB were dissolved in 2 mL of TEP, stirred at 65°C for 12 hours to obtain a polymer coating liquid. The mass proportion of LiBOB was 5%. The obtained polymer solution was passed through the liquid nozzle of the corresponding 3D printing equipment and sprayed on the side of the positive electrode away from the current collector to construct a three-dimensional lithium salt gradient polymer coating. The coating thickness was 15 μm.

[0110] Comparative Example 14

[0111] Example 1 was repeated, with the only difference being that: when designing the gradient solution coating in step (1), LiDFOB was used instead of LiBOB as the lithium borate, and TEP was used instead of TMP as the solvent. The same gradient solution was used in the preparation of the positive electrode polymer coating liquid. Specifically, 0.25 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight-average molecular weight of 400,000) and 0.126 g of LiDFOB were dissolved in 2 mL of TEP, stirred at 65°C for 12 h, and a polymer coating liquid was obtained. The mass proportion of LiBOB was 5%. The obtained polymer solution was passed through the liquid nozzle of the corresponding 3D printing equipment and sprayed on the side of the positive electrode away from the current collector to construct a three-dimensional lithium salt gradient polymer coating. The coating thickness was 15 μm.

[0112] The button cells prepared in Examples 1-9 and Comparative Examples 1-10 were used for performance testing, and the test results are as follows:

[0113] Table 1. Table of relevant performance test results of various embodiments and comparative examples

[0114]

[0115] By comparing Examples 1 to 9 and Comparative Examples 1 to 14 in Table 1, it can be seen that the positive electrode assembled solid-state battery prepared by spraying a gradient lithium borate phosphate polymer coating on the positive electrode side using the interface coating modification method has significantly reduced interface impedance at room temperature, fast ion migration rate, and small polarization during charge and discharge. Furthermore, at a current density of 2C, after 900 cycles, the capacity retention rate of Example 1 was 82.7%, which is significantly higher than that of the comparative example. At a high load positive electrode of 10 mg cm -2 It can be cycled stably for 200 times with a capacity retention rate of 96.13%. Even at an area capacity of 3.5 mAh cm -2 Under the condition of , the positive electrode assembled pouch battery with gradient structure polymer coating can maintain 82% of its initial capacity after 100 cycles, and the coulombic efficiency is 99.8±0.1%. By comparing Example 1 and Comparative Examples 9-10, it can be seen that lithium borates can effectively stabilize the structure of positive electrode active materials compared with common commercial lithium salts and achieve compatibility with high-voltage positive electrodes. By comparing Example 1 and Comparative Example 4, it can be seen that phosphate solvents can preferentially undergo electrochemical oxidation on the electrode surface compared with NMP, effectively forming a protective layer on the positive electrode surface. There is a synergistic effect between the two. LiBOB and LiDFOB are easily soluble in phosphate solvents such as TMP and TEP, and the prepared slurry has excellent electrochemical stability and thermal stability, improves the battery electrochemical window, and improves battery safety. The synergistic effect of the higher highest occupied molecular orbital (HOMO) energy level of phosphate solvents and the decomposition and film formation of lithium borates also enhances the interfacial stability of solid-state lithium metal batteries.

[0116] It can also be seen from the comparison between Examples 1-3 and Comparative Examples 1-3 that when gradient lithium borates are used, the room temperature impedance and electrochemical performance are the best. No gradient lithium borates were used in Comparative Examples 1-3, and the effect was not good. Among them, the lithium borate concentration in Comparative Example 1 is too low, resulting in a reduction in the number of ions that can be transmitted on the positive electrode interface side, reducing the ion mobility, which is manifested as a room temperature impedance of 173Ω, and the battery has poor cycle performance. In Comparative Example 3, the lithium borate concentration is too high, the Young's modulus is low, the mechanical strength of the polymer coating is reduced, and the growth of lithium dendrites cannot be effectively inhibited. Although the increase in lithium salt concentration helps to dissociate more lithium ions, the long cycle performance of the battery is not good, and it only cycles 473 times at 2C. In addition, it can be seen from the comparison between Example 7 and Comparative Example 12, Example 8 and Comparative Example 13, and Example 9 and Comparative Example 14 that when different lithium borates and phosphate solvents are used, the room temperature impedance and electrochemical performance exhibited by the gradient lithium borate design are also better.

[0117] By comparing Examples 4-6 and Comparative Examples 5-8, it can be seen that when the thickness of the polymer coating is designed to be too thin in Comparative Example 5, the battery only cycles 215 times at 2C, and the coating cannot effectively adapt to the volume change of the positive electrode material, resulting in the polymer coating breaking and failure. When the thickness of the polymer coating is designed to be too thick in Comparative Example 6, the battery dives after 610 cycles at 2C, indicating that the coating is too thick, which is not conducive to the transmission of ions, hinders the insertion / extraction of lithium ions, and reduces the reaction kinetics of the interface.

[0118] like Figure 6 As shown, in Example 1 of the present invention, the positive electrode is 10 mg / cm 2 Room temperature electrochemical performance of assembled button cells under high load, with a positive electrode load of 10 mg cm -2 , it can stably cycle 200 cycles in the voltage range of 3-4.2V, and the capacity retention rate is 96.13%, showing excellent cycle performance.

[0119] like Figure 7 As shown, in Example 1 of the present invention, the area capacity is controlled to be 3.5 mAh cm -2 Under the condition of high temperature, the positive electrode assembled pouch cell with gradient structure polymer coating can maintain 82% of its initial capacity after 100 cycles, and the coulombic efficiency is improved to 99.8±0.1%, which is of great value for industrial application.

[0120] The solid-state batteries prepared in Example 1 of the present invention and Comparative Example 11 were tested for room temperature impedance, CV performance, first cycle charge and discharge curve, and cycle performance at 2C. The results are as follows: Figure 2 , Figure 3 , Figure 4 , Figure 5As shown in the figure, the solid-state battery prepared by the conventional solution casting method has a room temperature impedance of 620Ω, a large polarization during the charge and discharge process, and only cycles 260 times at a low load of 2C, and cannot be temperature cycled at 0.5C under a high load of the positive electrode. The gradient structure design using 3D printing equipment shows low impedance, low polarization and excellent electrochemical performance, which fully demonstrates that the polymer coating prepared by 3D printing stabilizes the positive electrode structure and reduces polarization and impedance.

[0121] It should be noted that the above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A composite positive electrode sheet, characterized in that: It includes a positive electrode and a coating located on the surface of the positive electrode away from the current collector, wherein the coating includes 2-5 polymer layers, each of which includes lithium borate, and the concentration of lithium borate in the polymer layers decreases in a gradient, and the concentration of lithium borate in the polymer layer closest to the positive electrode is the highest.

2. The composite positive electrode sheet according to claim 1, characterized in that: The polymer coating comprises a polymer matrix solution and lithium borate; the polymer matrix solution comprises a polymer matrix and a phosphate ester solvent.

3. The composite positive electrode sheet according to claim 1, characterized in that: The polymer matrix is ​​selected from any one or two of polyvinylidene fluoride and poly (vinylidene fluoride-hexafluoropropylene) copolymer; the lithium borate is selected from any one or two of lithium bis(oxalatoborate) and lithium difluorooxalatoborate; and the phosphate solvent is selected from any one or two of trimethyl phosphate and triethyl phosphate.

4. The composite positive electrode sheet according to claim 1, characterized in that: The weight proportion of lithium borate in the polymer coating for preparing the polymer layer closest to the positive electrode is 7-9 parts.

5. The composite positive electrode sheet according to claim 1, characterized in that: The weight proportion of lithium borate in the polymer coating for preparing the polymer layer farthest from the positive electrode sheet is 1-3 parts.

6. The composite positive electrode sheet according to any one of claims 1 to 5, characterized in that: The coating comprises three polymer layers; the weight proportion of lithium borate in the polymer coating for preparing the middle layer is 4-6 parts.

7. The composite positive electrode sheet according to any one of claims 1 to 5, characterized in that: The coating includes 4 polymer layers; the polymer coating for preparing the second polymer layer closest to the positive electrode sheet has a lithium borate mass ratio of 5.5-6.5 parts; the polymer coating for preparing the third polymer layer closest to the positive electrode sheet has a lithium borate mass ratio of 3.5-5 parts.

8. The method for preparing a composite positive electrode sheet according to any one of claims 1 to 7, characterized in that: The following steps are involved: The polymer coatings containing different concentrations of lithium borate are fixed on the surface of the positive electrode away from the current collector in sequence through 3D printing gradient. The polymer coating with the highest lithium borate concentration is printed on the inner side close to the positive electrode to form a gradient structure coating.

9. The preparation method according to claim 8, characterized in that: The total thickness of the printed coating was 10-25 μm.

10. A solid-state battery, characterized in that: Comprising the composite positive electrode sheet according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Composite positive plate, preparation method thereof and solid-state battery

    CN111952597A

  • Solid-state battery and preparation method thereof

    CN118867413A